The relationship between exercise motivation and exercise behavior in college students: The chain-mediated role of exercise climate and exercise self-efficacy - Zhao, Yu Shun; Ma, Qi Shuai; Li, Xing Yi; Guo, Ke Lei; Chao, Liu (Frontiers in Psychology, 2023)
Objective This study explored the relationship between college students’ physical activity motivation and exercise behavior and constructed a chain mediation model through the mediating roles of exercise climate and exercise self-efficacy. Methods By random sampling, 1,032 college students were investigated using the Exercise Motivation Scale, Physical Exercise Rating Scale, Exercise Climate Scale, and Exercise Self-Efficacy Scale. Results (1) There was a huge positive correlation between exercise motivation and exercise behavior (r = 0.240, p < 0.01), and the immediate ways of linking exercise motivation to exercise behavior were critical (β = 0.068, t = 0.040, p < 0.01). (2) Exercise motivation could positively predict exercise climate (β = 0.373, t = 0.061, p < 0.01) and exercise self-efficacy (β = 0.174, t = 0.039, p < 0.01), and exercise climate could emphatically foresee exercise behavior (β = 0.302, t = 0.051, p < 0.01). Exercise self-efficacy could foresee exercise behavior decidedly (β = 0.190, t = 0.048, p < 0.01). (3) Exercise climate and exercise self-efficacy play a critical intervening role between exercise motivation and exercise behavior. The intercession impact is explicitly made out of aberrant impacts created in three ways: exercise motivation → exercise climate → exercise behavior (mediating effect value: 0.113); exercise motivation → exercise self-efficacy → exercise behavior (mediating effect value: 0.033); exercise motivation → exercise climate → exercise self-efficacy → exercise behavior (mediating effect value: 0.027). Conclusion (1) Exercise climate, exercise self-efficacy, and exercise behavior can all be significantly predicted by exercise motivation, suggesting that exercise motivation may help to enhance these variables. (2) In addition to having a direct impact on exercise behavior, exercise motivation can also have an indirect impact through the separate mediating effects of exercise climate and exercise self-efficacy as well as the chain mediating effect of exercise climate and exercise self-efficacy, which is crucial for encouraging college students to engage in physical activity.